2022
DOI: 10.3389/fnano.2022.1023489
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic degradation of tetracycline antibiotic over a flower-like S-doped BiOBr: Performance, mechanism insight and toxicity assessment

Abstract: A new catalyst of S-BiOBr flower-like morphology was synthesized by simple pyrolysis and further used for photocatalytic degradation of TC. Phase structure analysis, elemental analysis and micromorphological analysis confirmed that S doping has a reinforcing effect on the polarization between the [Bi2O2S]2+ and [Br2]2- layers and is conducive to interlayer polarization and rapid charge transfer. In addition, its unique petal morphology is more favorable to the adsorption of contaminants on its surface and acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Thereby, the enhanced degradation efficiency by MIN3 and MIN4 can be attributed to the specific binding of TC at molecularly imprinted cavities, minimizing the loss of oxidative potential due to ROS diffusion or deactivation. , MIN4 showed a better performance in promoting TC than MIN3 , in line with the TC rebinding capacity of these nanomaterials (Figure ). Regarding degradation products, literature reports have shown that the oxidative processes triggered by singlet oxygen and other ROS result in low molecular weight nontoxic compounds. The proposed degradation pathways involve the oxidation of the N , N -dimethyl group into a carbonyl derivative and the subsequent removal of the amide moiety in ring A, followed by subsequent ring fragmentations. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thereby, the enhanced degradation efficiency by MIN3 and MIN4 can be attributed to the specific binding of TC at molecularly imprinted cavities, minimizing the loss of oxidative potential due to ROS diffusion or deactivation. , MIN4 showed a better performance in promoting TC than MIN3 , in line with the TC rebinding capacity of these nanomaterials (Figure ). Regarding degradation products, literature reports have shown that the oxidative processes triggered by singlet oxygen and other ROS result in low molecular weight nontoxic compounds. The proposed degradation pathways involve the oxidation of the N , N -dimethyl group into a carbonyl derivative and the subsequent removal of the amide moiety in ring A, followed by subsequent ring fragmentations. …”
Section: Resultsmentioning
confidence: 99%
“…Regarding degradation products, literature reports have shown that the oxidative processes triggered by singlet oxygen and other ROS result in low molecular weight nontoxic compounds. 67 69 The proposed degradation pathways involve the oxidation of the N , N -dimethyl group into a carbonyl derivative and the subsequent removal of the amide moiety in ring A, followed by subsequent ring fragmentations. 67 69 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation